Optimising process flow in manufacturing: a study on standardisation and equipment capacity - Samakova, Jana; Babcanova, Dagmar; Czibula, Norbert (Acta logistica, 2025)
The main goal of a manufacturing company is to make a profit, which requires efficient in-house processes and smooth process flow. The key tools for increasing productivity and optimizing production are process standardization, workflow efficiency, and the application of the theory of constraints (TOC). Process standardisation leads to the standardisation of workflows and the elimination of variability. TOC focuses on identifying bottlenecks in the process and optimizing them, resulting in cost reduction, increased productivity, and improved enterprise profitability by enhancing process flow. The presented paper describes a case study aimed at analysing selected processes at robotic welding workstations in a selected industrial enterprise. The aim of the paper is to identify opportunities to improve production efficiency at robotic welding workplaces, focusing on standardization of work procedures, more efficient use of production equipment capacity, and improvement of the remuneration system, which has a direct impact on workflow efficiency, process optimization, and the financial performance of the enterprise. The results of the research point to a lack of standardisation of working practices, low utilisation of the equipment capacity (30% below the planned value) and limitations in the remuneration system that hinder the achievement of the full productivity potential. The combination of inefficient use of equipment and working time increases financial costs and limits profitability. An effective bonus system can increase employee motivation, support productivity improvements and contribute to cost reduction. To address these issues, the implementation of standardised work practices, optimisation of equipment utilisation and effective workforce management are needed.